How successfully do immigrant parents transfer their voting behavior to their offspring? - Monika Bozhinoska Lazarova; Christoph Spörlein (Frontiers in Political Science)
This study integrates political socialization theory and behavioral genetics to disentangle the mechanisms underlying differences in the intergenerational transmission of voter turnout in majority and immigrant families. The pathways shaping the intergenerational transmission of electoral participation are examined through variations in political exposure within families, offspring’s social engagement in the host country, and the socioeconomic status of the family. We base our analysis on data from the German TwinLife study, comparing majority adolescents with first-generation, second-generation and 2.5th generation immigrants using a genetically sensitive multilevel research design. Focusing on electoral participation, we find that within-family transmission is disrupted for second-generation and 2.5-generation immigrants, whereas there is no difference between native citizens and first-generation immigrants. Taken together, within-family political exposure, social engagement and socioeconomic status only weakly explain the observed gap in intergenerational transmission.